2018
DOI: 10.1136/bcr-2017-223996
|View full text |Cite
|
Sign up to set email alerts
|

3D printing for corrective osteotomy of malunited distal radius fractures: a low-cost workflow

Abstract: After a severe trauma, a 16-year-old female patient sustained multiple injuries, including a distal radius fracture of the left arm. This distal radius fracture eventually developed into a malunion. In this case, we demonstrate our preoperative low-cost workup for three-dimensional (3D) planned and assisted corrective osteotomy of a malunited distal radius fracture using an in-hospital 3D printer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…Even when the resulting surgical technique is similar, the location of incisions and the design of the osteotomy are refined to reflect decisions made during practice on the models. Overall, 3D-printed models allow for reduced operating room time and improved clinical outcomes in a majority of patients, with a downside often being increased costs 8, 17. The authors found practicing the correction on the 3D-printed model to be especially useful in planning the rotational portion of the correction, as noting the offset created at the desired rotation of the osteotomy provided another way of confirming appropriate alignment during the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even when the resulting surgical technique is similar, the location of incisions and the design of the osteotomy are refined to reflect decisions made during practice on the models. Overall, 3D-printed models allow for reduced operating room time and improved clinical outcomes in a majority of patients, with a downside often being increased costs 8, 17. The authors found practicing the correction on the 3D-printed model to be especially useful in planning the rotational portion of the correction, as noting the offset created at the desired rotation of the osteotomy provided another way of confirming appropriate alignment during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple examples can be found utilizing 3D-modeling software and 3D-printed surgical guides for preoperative planning and intraoperative assistance, but few go so far as to practice the surgical plan on an anatomically correct model 13, 20, 21, 23, 24. In those examples where 3D-printed modeling is used extensively, the patients in question are usually adults 6, 8. In addition, computed tomography is often used to create the 3D model 8, 13, 17, 20, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of motion of the wrist was improved to 80° extension and 55° flexion, and the disability of the arm, shoulder, and hand score improved from 12 preoperatively to 7 out of 100 during one year after the surgery. So, they recommend the 3D printing method in a case with minimal exposure to bone cortices. , …”
Section: Toward Personalized Medicine From Regenerative Medicinementioning
confidence: 99%
“…The usage and breadth of 3D printing applications is increasing in Western healthcare settings (Brouwers et al, 2018b;Choong et al, 2020;Fransen, 2015;Inge et al, 2018;Long Ng et al, 2019;Ng et al, 2018;Tack et al, 2016;Trenfield et al, 2019; UZ Leuven, 2016). Notwithstanding, in low-resource settings, the prospects of 3D printing devices in healthcare remain by-and-large underexploited (Schonwetter and Wiele van, 2018).…”
Section: Introductionmentioning
confidence: 99%